PERAN PUSTAKAWAN DALAM MEMBANGUN MASYARAKAT LITERER PADA HARI KUNJUNG PERPUSTAKAAN - Sutarsyah Sutarsyah (Perpustakaan Nasional RI, 2016)
Information literacy is a set of skills required for recognizing when information is needed, where information is retrieved from, and how information is evaluated and used effectively. Information literacy is a basic need in lifelong learning process. This article describes the importance of information literacy in public and a well-organized library visit day exhibition. The event is a proper way to promote library services and a medium for public interaction in order to invite them to visit and use library facilities and services. It is expected that the exhibition will be able to encourage information literate people to use libraries optimally.